2020
DOI: 10.1016/j.jmii.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological features, clinical characteristics and outcomes of infective endocarditis in adults with and without hemodialysis: A 10-year retrospective study in Northern Taiwan

Abstract: Advanced age, sex (female), comorbidities, diabetes mellitus, and hypertension were more common in HD patients than in non-HD patients with IE. HD patients had higher proportion of methicillin-resistant S. aureus and cardiac complication rates than non-HD patients with IE. Culture-negative IE was more common in non-HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Staphylococcus aureus has been reported to be the predominant causative pathogen of IE in chronic dialysis patients. 8,22 Consistent with this finding, S. aureus was the most common organism (35.3%) in our study group. Moreover, MRSA endocarditis reportedly has higher mortality than endocarditis that is caused by most other microorganisms.…”
Section: Dovepresssupporting
confidence: 90%
“…Staphylococcus aureus has been reported to be the predominant causative pathogen of IE in chronic dialysis patients. 8,22 Consistent with this finding, S. aureus was the most common organism (35.3%) in our study group. Moreover, MRSA endocarditis reportedly has higher mortality than endocarditis that is caused by most other microorganisms.…”
Section: Dovepresssupporting
confidence: 90%
“…A previous study reported that the causative pathogen is S. aureus in 40–63.6% of haemodialysis patients with IE, and haemodialysis patients have a higher proportion of MRSA than non-haemodialysis patients. 20 The present study identified the microbiological aetiology of IE as MRSA and Enterococcus in the majority of haemodialysis patients. By contrast, Streptococcus was the main pathogen in non-haemodialysis patients during the same period.…”
Section: Discussionmentioning
confidence: 82%
“…Although a small number of clinical markers were reported to not be responsible for the mortality and occurrence of MAEs in this population (5,11,12), the role of glucose levels and variability has not yet been investigated. Glucose levels are frequently monitored in the ICU, which makes GV a simple and cost-effective indicator for the prognostic Variables of postoperative glycemic fluctuation are presented as medians (interquartile range), the enumeration data are presented as n (%).…”
Section: Discussionmentioning
confidence: 92%
“…The univariate analysis indicated that postoperative MAEs were associated with age, systemic emboli, staphylococcus infection, uncontrolled infection, prosthetic valve endocarditis, emergency surgery, vegetation size ≥10 mm and both mitral and aortic involvement. In the previous studies, these risk factors were reported to be associated in varying degrees with the outcomes of IE patients (12,14,15). On the other hand, although in the current study hemoglobin A1c did not show any significant difference between patients with and without MAEs, the study by Subramaniam et al demonstrated that preoperative hemoglobin A1c identifies the risk for postoperative glycemic variability and had somewhat of an effect on the incidence of MAEs following bypass surgery (16); thus, we also included hemoglobin A1c in our model to minimize its influence on postoperative glycemic variability.…”
Section: Evaluation Of Ie Patients a Meta-analysis Of Twelvementioning
confidence: 99%